Linkage Analysis between Solid-Fluid Coupling and the Strength Reduction Method for Karst Cave Water Inrush in Mines - Yanlin Zhao; Jian Liao; Qiang Liu; Yang Li; Jianchao Cheng (Shock and Vibration)
The present paper aims to study the mechanical mechanism and characteristics of water irruption from Karst cave. Combining the nonlinear seepage-pipe coupling model with the strength reduction method, the linkage analysis of fluid solid coupling and strength reduction method are constructed to study the whole process of confined Karst cave water inrush. Taking the water inrush accident of Shibaijing of the Qiyi mine in south China as an example, the instability mechanism of the water-proof rock pillar and evolution of water inrush are discussed. It is suggested that water discharge on the working face augments with the increase in the reduction factor of the water-proof rock pillar before the rock pillar loses its stability. Once the rock pillar becomes unstable, Karst water bursts from confined Karst cave in a pipe flow shape, and the water irruption quantity reaches the peak value in a short time by adopting the pipe flow to simulate and then decreases slowly. The hydraulic rough flow at the initial stage changes into pipe laminar flow finally in the process of Karst water inrush, due to the constraint of Karst cave water reserve. The conception for the safety factor of the water-proof rock pillar introduced, the relation of the safety factor, Karst cave water pressure, and thickness of the water-proof rock pillar are studied. It is proposed that thickness of the water-proof rock pillar whose safety factor equals 1.5 is regarded as the calculating safety thickness of the water-proof rock pillar, and the safety thickness of the water-proof rock pillar setting in mining engineering should be equal to the sum of the blasthole depth, blasting disturbance depth, and the calculating safety thickness. The reason leading to Karst water inrush of Qiyi Mine is that without advanced boreholes, the water-proof rock pillar is set so small that it could not possess safety margin, so the confined Karst cave water breaks the water-proof rock pillar and bursts out. Combining the solid fluid coupling theory, pipe flow theory, and strength reduction method, the nonlinear mechanical response of confined Karst cave water inrush is studied, which provides a new study method for the whole process of confined Karst cave water inrush.